Draft Annual Plan 1975-76 Vol. I (Part II) Government of Manipur - Planning Commission (Planning Commission, 1974)
The Fifth Plan outlay of the Manipur State is tentatively of the order of Rs.92.83 crores of which an outlay of Rs.25.22 crores has been proposed for the Annual Plan, 1975-76. The Draft Annual Plan, 1975-76, has been presented in three Volumes. Volume-I is in narrative fern and contains seven chapters. The introductory chapter gives an overall survey of the socio-economic situation of the State with measures proposed to be taken to make optimum use of the available resources. Chapter II gives the resources of the State, while the sectoral programmes have been discussed in detail in Chapter-III. Minimum needs Programme and the programmes of Hill/Tribal areas have beau dealt in the fourth and fifth chapters respectively. Also,, a separate chapter has been added, dealing with the problems of aid remedial measures against Natural Calamities. Lastly, the Administrative Policy and Institutional framework are dealt in chapter VII.
Government of Manipur
Planning & Development Department
Keywords: Social Services; Intograted Nutrition Programme; Special Nutrition Programme; Housing; Urban Development; Welfare of Backward Classes; Social Welfare; Employment and Labour; Health; Education